Analysis of Students' Understanding of Concepts on Momentum and Impulse Material Using Research-Based Learning (RBL) Models - Safarati, Nanda; Rahma, Rahma (Universitas Ahmad Dahlan, 2020)
This study aims to analyze students' understanding of concepts in the material of momentum and impulses using research-based learning (RBL) models. This type of research is quantitative research with a descriptive approach. The population in this study were students of class XI of SMA 3 Bireuen, the subjects in this study were students of class XI2 of SMA 3 Bireuen as many as 30 students. The results of this study indicate that 30 students in class XI2. 53.3% of students in the category understood the concept, 20% students in the guessing category and 26.7% students in the don't understand the category. This shows students will better understand the concepts of momentum and impulses by using research-based learning models.